Development of a Nursing Management Model for Trauma Patients in the Maha Sarakham Provincial Network - Sripontan, Julintorn; Somgit, Wuttichai; Klungprasri, Paramaporn; Kaewaroon, Wilaiphon; Namboonruang, Thanisssara; Charoensiri, Kanokwan; Phraphatphong, Sirinard (Princess of Naradhiwas University Journal, 2025)
Participatory action research aimed to develop a nursing management model for trauma patients in the Maha Sarakham provincial network and was divided into three phases: 1) Situation analysis, 2) Development of the nursing management model, and 3) Evaluation of the developed model. The sample group consisted of 109 trauma patients receiving treatment at hospitals in Maha Sarakham province who met the specified criteria, 157 professional nurses caring for trauma patients, and 449 basic life support unit staff. The study was conducted from January 2022 to December 2025. Research tools included focus group discussion guidelines, observation forms for adherence to the nursing management model, trauma patient data recording forms, professional nurse competency assessment forms, basic life support unit staff competency assessment forms, and questionnaires on opinions regarding the nursing management model. Data were analyzed using percentages, means, and content analysis. The research findings revealed that 1) in the situational analysis phase to identify problems, issues were found regarding trauma patient’s access to the service system, the absence of a nursing management model for trauma patients, problems related to nursing competencies and assistance for trauma patients, and a lack of information transfer channels within the network; 2) the nursing management model for trauma patients that was suitable for the Maha Sarakham provincial network was developed; and 3) evaluation results showed that the outcomes of patient care have improved. Professional nurses and staff from the basic life support unit have increased competencies in caring for trauma patients, and professional nurses were highly satisfied with the developed nursing management model at the highest level, 100%. Therefore, the developed nursing management model should be implemented in networks with similar contexts.